Peningkatan Hasil Belajar Siswa Melalui Model Contextual Teaching And Learning Madrasah Ibtidaiyah Model Panyabungan - Syafrilianto Syafrilianto; Miftah Khairani Tanjung; Siti Zubaidah Siregar (Gravity Journal, 2022)
This study aims to improve student learning outcomes in class III MI Panyabungan Model. The type of research used in this research is classroom action research (CAR) using Kurt Lewin's model which consists of four stages, namely the planning stage, the action implementation stage, the observation stage, and the reflection stage. The results showed that in the pre-cycle before the action, only 20% of the students who achieved completeness were. In cycle 1, meeting 1, after applying the contextual teaching and learning model, students who completed the KKM (70) were 5 students or (33.33%) while in cycle 1, meeting 2, students who completed the KKM (70) were 7 students or (46, 66%) . In the second cycle of meeting 1 learning using the contextual teaching and learning model of students who completed the KKM (70) as many as 10 students or (66.66%) while in the second cycle of the second meeting the students who completed the KKM (70) were 13 students with a percentage (86, 66%). So it can be concluded that the Contextual Teaching and Learning learning model can improve student learning outcomes in science learning the material for changing the shape of objects in class III MI Panyabungan Model.